The success of ornamental coral propagation in Banyuwangi East Java, Indonesia: observation of different depths and species - Johan, Ofri; Ginanjar, Rendy; Budiyanto, Agus; Ardi, Idil; Priyadi, Agus; Kunzmann, Andreas (Frontiers in Marine Science, 2023)
Ornamental corals have become the main attention objects for many hobbyists and have already become a source of country foreign exchange. Through ornamental coral propagation, the continuity of ornamental coral trade can be guaranteed and the level of damage can be overcome. The propagation technique has been developed by ornamental coral exporters in several locations in Indonesia. The study showed that corals can grow optimal and have exotic colors when placed at different depths. Best coral growth was obtained from fast-growing coral species at a shallow depth (0-5 m). While medium depth (5-10 m) was suitable for corals with moderate growth rates and on the other side, the deeper depths (10-25 m) are characterized by bright-colored corals with slow-growing rates. Color quality and growth of corals are closely related to some supporting factors such as the suitability of locations that have different physical, biological, and chemical factors between depths and it takes different requirements among coral species. Location choices determine the success of coral cultivation both for ornamental. These pieces of information are important for traded ornamental corals that can be utilized by propagators.